Consumer Preferences for OTT Platforms in India: A Behavioral Study - Sinha, Gaurav Kumar (Journal of Global Economy, Business and Finance, 2026)
This research paper aims to provide thorough insights into the potential of Indian viewers about Over-The-Top (OTT) platforms. With 231 replies from the general public. This survey is conducted in Indian and the top 5 OTT providers in India is considered, which include Jio Cinema, Netflix, Amazon Prime, Hotstar, and Zee5. And attempts to figure out the reasons behind Indian audience on selecting these providers over competitors. The research proposes discussing how your decision to use an OTT platform is influenced by the Factors influencing their preference, the types of content watch on OTT platforms and how often do they use OTT platforms. Also, considering the age group and educational qualifications of the respondent. By revealing the complicated relationship between each of those elements, this study not only provides priceless insights into the nature of the Indian OTT Platform, but also addresses issues concerning the transformed viewing habits of the people in India, eventually contributing to a deeper understanding of the growth of the Indian entertainment industry.